What makes a community sustainably developed? A review of 25 years of sustainable community tourism literature. Issue 5 (20th October 2022) - Dogra, Nikhil; Adil, Mohd; Dhamija, Aruna; Kumar, Mukesh; Nasir, Mohd
ABSTRACT: The purpose of this study is to offer a comprehensive understanding of community development. We conducted a thorough review of 25 years of sustainable community tourism literature, examining about 110 published articles. Besides synthesizing the essential indicators that shape sustainable community development, this review also outlines some of its key benefits and challenges. Holistically, the review presents a broader perspective about socio-environmental as well as economic indicators of sustainable community development, while focusing on elements that are effectively necessary to implement sustainability. Importantly, this review adds to the growing body of knowledge, while lending crucial insights in terms of practical implications, which we believe would enable policymakers to both consider and comprehend community development through the lens of sustainable tourism at regional and remote destinations.